Rethinking social action through the info-ecological dimensions of two collaborative public health platforms: the people’s health movement and the citizen sense project platforms as examples of health-net-activism - Silvia Surrenti; Massimo Di Felice (Frontiers in Sociology)
IntroductionThe analysis of online platforms is usually restricted to their communicative properties, similar to analyzing digital infrastructures that facilitate interactions among users. However, the definition is missing a broader interpretation rather than tools or communicative channels. To review this instrumental vision, scholars in a variety of fields have begun to analyze platforms from a multidisciplinary perspective as technical, economic, and sociocultural ecosystems that characterize the structure of contemporary society.MethodsIn this article, we adopt an info-ecological approach to the processes of platformization through a qualitative analysis of two platforms dedicated to health and quality of life. The infoecological approach suggests a new living condition that promotes the emerging computational ecologies composed of a web of people, data, algorithms, biodiversity, information, cities, viruses, and so forth, supporting a more-than-human common experience.Results and discussionThe purpose is to examine how the heterogeneity of platform ecosystems (human and non-human) have been generating a cultural shift. That is to say, a-more-than-human interconnected and trans-organic network of networks that in our perspective also represent what we have called a new type of health-net-activism and digital citizenship.